SPAYING AND NEUTERING DOGS AND CATS AS A ONE HEALTH TOOL - Lopes, Ramyla Thalia de Assis; Menezes, Maria Luiza de Souza; Ribeiro, Maria Joana Darc do Nascimento; do Nascimento, Nathaly Larissa Oliveira; da Rocha, Pollyana Nibbering Ferreira; de Lima, Laura Militão; de Souza, Wender José Vital de Athayde; Silva, Flaviane Maria Florêncio Monteiro; Soares, Anísio Francisco; da Silva, Elayne Cristine Soares (Seven Editora, 2026)
The bond between humans and animals has grown, and many are now considered family members. This relationship brings emotional, social, and physical benefits to those responsible, but it also requires responsible pet ownership practices such as vaccination, deworming, proper nutrition, and, above all, sterilization. Failure in these areas contributes to animal abandonment, overpopulation of stray dogs and cats, the spread of zoonotic diseases, and negative impacts on public and environmental health. In this context, the One Health concept becomes fundamental by integrating human, animal, and environmental health. Sterilization stands out as one of the main strategies for population control, prevention of reproductive diseases, reduction of neoplasms, improvememt of animal behavior, and increased life expectancy of pets.